PEMBINAAN PRESTASI CABANG OLAHRAGA BASKET KLUB SMA NEGERI 2 TEBING TINGGI KEPULAUAN MERANTI - Lestari, Yunita Ade; Sulastio, Agus; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research was conducted using a quantitative descriptive surveymethod. This research was conducted at SMA Negeri 2 Tebing Tinggi which is locatedat Jalan Tutwuri, Selat Panjang Tim., Kec. Tebing Tinggi, Meranti Islands Regency,Riau. This research was conducted from February 2023 to March 2024. The populationin this research was 22 students from SMA Negeri 2 Tebing Tinggi, using a samplingtechnique, namely saturated sampling or total sampling. This research instrument usesa questionnaire or questionnaire with data analysis in the form of percentages. Basedon the results of the research and data processing carried out, it can be concluded asfollows: Based on the graph above, it shows that the development of basketballachievements at SMA N 2 Tebing Tinggi based on external factors is in the "stronglydisagree" category at 6.25%, the "disagree" category. 25%, the "fair" category is31.25%, the "agree" category is 31.25%, the strongly agree category is 0%, based onthe average value, namely 170.5625 coaching achievements in basketball at SMA N 2Tebing Tinggi Based on external factors, there are categories with the same value,namely the "sufficient" and "agree" categories with a percentage of 31.25%.Keywords: Achievement Development, Basketbal